KEADILAN DALAM HUKUM LEX TALIONIS: TAFSIR TERHADAP KELUARAN 21:22-25 - Firman Panjaitan; Marthin S. Lumingkewas (Sekolah Tinggi Alkitab Tiranus, 2019)
The Lex Talionis law is often understood as a law that applies maximum revenge. Through this law, all forms of retaliation are legalized and even justified. The study in Exodus 21: 22-25 just wants to show the opposite of the above understanding. According to the word talion, indeed the Lex Talionis law presupposes complete retaliation. But through interpretation and excavation, especially on Exodus 21: 22-25, the main elements found in Lex Talionis’ law are found; which does not refer to a complete attempt to retaliate, but instead points to the aspect of God's justice in response to every legal case that applied between humans. Thus, the Lex Talionis law is no longer seen as a law of retaliation, but a law of justice that allows this type of law to be implemented in today's life. The results of the study using narrative interpretation methods and combined with textual criticism resulted in an understanding that Lex Talionis law had practical implications, especially regarding the value of sosial justice that could be submitted to the perpetrators of injustice through the courts, so justice would be expected.